Temporal Sequencing Abilities in Musicians Violinists and Non-Musicians - Nascimento, Franklin Martins; Monteiro, Ricardo Alexandre Martinez; Soares, Carla Debus; Ferreira, Maria Inês Dornelles da Costa (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: The ability of temporal sequencing refers to the processing of two or more auditory stimuli in order of occurrence in time.Objective: To compare the skill of sequencing between musicians and non-musicians violinists from the frequency pattern test (FPT).Method: The prospective, constituted a group of 20 violinists and musicians non-musicians 20 participants, half matched for age and education, all males who underwent audiometric assessment and WPPT.Results: Comparing the performance in TFP between the groups was found statistically significant for the group of musicians in both ears, (p = 0.003) for the right ear (RE) and (p = 0.002) for the left ear (OE). The results of the PPT were correlated with the average frequencies, three-tone average and high frequencies mean obtaining a statistically significant only for OD being (p = 0.0047) for low frequencies, (p = 0.011) for average and tritonal (p = 0.02) for the average frequencies. The comparative analysis between the ears, the only group statistically significant variable was the mean of frequencies in the group of musicians (p <0.001).Conclusion: The performance of the group of musicians in the TPF group was superior to non-musicians. Highlights the relevance of the auditory thresholds for low frequencies, acute tritonal average performance of TPF in OD.
Keywords: music; auditory threshold; hearing tests; auditory perception